Factors that Influence Student Interest in Participating in Usimar Campus UKM Activities - Askahar, Askahar; Yusuf, Muhammad; Akmir, Akmir (PT FORMOSA CENDEKIA GLOBAL, 2024)
Factors that influence students' interest in participating in Student Activity Unit (UKM) activities at the Islamic Science University (USIMAR). This study uses qualitative research methods by conducting interviews with students in various faculties. The results of the interviews show that student interests and factors are closely related to each other. Supportive factors from the environment, such as encouragement from peers and family support, have a positive influence on students' interest in participating in UKM activities. Apart from that, the benefits obtained from participation in UKM are also an important factor that motivates students. This research provides in-depth insight into the dynamics of student interest in participating in UKM activities on the USIMAR campus environment. The implications of these findings can be used by campuses and UKM managers to increase student participation and strengthen the sustainability of UKM as a means of developing student potential outside academic activities